ANALISIS PENGARUH STRUKTUR ASET, PERTUMBUHAN ASET, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Levina Aurelia, Herlin Tundjung Setijaningsih (Jurnal Paradigma Akuntansi, 2020)
The aim of this research is to examine the effect of asset structure, asset growth and firm size to capital structure of manufacture companies listed on Indonesia Stock Exchange for the period 2014-2017. Sampe wasselected using purposive sampling method amounted to 91 companies. Data processing techniques using multiple regression analysis what  helped  by  SPSS  program  (Statistical  Product  and  Service  Solution)  for  Windows released 22. The result of this study show partially assets structure have significant effect to capital structurewhile asset growth and firm size have no significant impact to capital structure. However this study shows that simultaneously assets structure, assets growth and firm size have a significant effect on capital structure.